Follicular lymphoma: diagnosis, treatment, and follow-up - Zoellner, Anna-Katharina; Herfarth, Klaus; Herold, Michael; Klapper, Wolfram; Skoetz, Nicole; Hiddemann, Wolfgang (Deutsches Ärzteblatt, 2021)
Background: Follicular lymphoma (FL) occurs predominantly at advanced age, with an annual incidence of 3-5 cases per 100 000 inhabitants in Western countries. The clinical course is heterogeneous. - Methods: For this new guideline, systematic literature searches were conducted in medical databases (MEDLINE, PubMed Central) (up to November 2017) and in the Guidelines International Network (G-I-N), and recent publications were added. - Results: The results of 21 systematic reviews with meta-analyses, 75 randomized controlled trials, and 58 prospective and retrospective studies were evaluated. Lymph-node biopsy is necessary for initial diagnosis of FL. CT scanning of the neck, thorax, and abdomen should be performed to assess how far the disease has spread, together with bone marrow biopsy and, if required, PET/CT. In early FL (stages I and II; 10-15 %), potentially curative radiotherapy combined with an antiCD 20 antibody is recommended. In advanced disease (stages III and IV), watchful waiting is indicated for patients who have no clinical symptoms and a low tumor burden. Patients with clinical symptoms and/or high tumor burden should receive chemotherapy in combination with an anti-CD 20 antibody, followed by 2 years’ maintenance treatment with an anti-CD 20 antibody. - Conclusion: Given the good long-term prognosis of FL, the treatment must be chosen with care and thorough follow-up is necessary to ensure detection of late sequelae such as second malignancies or organ damage.